Deskripsi Pemanfaatan Multimedia Interaktif dalam Pembelajaran: Studi pada Mahasiswa Pendidikan Matematika - Asyura, Ira (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the use of interactive multimedia in learning by students of the Mathematics Education Program at STKIP Syekh Manshur. This research employs a qualitative approach with a descriptive method. The research subjects consist of 14 students enrolled in the Media and Mathematical Teaching Aids course during the Odd Semester of the 2024/2025 academic year. In the course, students were introduced to and trained in the use and development of various interactive multimedia tools, including VBA PowerPoint, GeoGebra, Smart App Creator, and Scratch, as a means of designing mathematics learning media. Data collection techniques included classroom observation, student work documentation, and a questionnaire to gather student responses using interactive multimedia. Data analysis using qualitative descriptive analysis with the percentage of student responses to the use of interactive multimedia. The results show that using interactive multimedia encourages active student engagement, enhances creativity in designing learning media, and strengthens their understanding of mathematical concepts. The questionnaire responses indicate that using these multimedia tools is considered engaging, facilitates understanding, and provides hands-on experiences that are relevant to the competencies of future mathematics teachers